The Imperial Reserve The Indian Infantry on the Western Front., 1914- 15 - Greenhut, Jeffrey (Kansas State University, 1978)
In the course of my studies leading to this dissertation, I have incurred great debts to many people, and it would be impossible to mention all of them. However, it is my great pleasure to acknowledge some. While all the members of the History Department of Kansas State University, as well as a few from the Department of Anthropology, and of Modern Languages have been of help to me, two in particular deserve special mention. My major Professor, Dr. Robin Higham, made a great contribution to all my studies and to this dissertation. So did Professor Kenneth Jones who taught me what a historian is supposed to do and be. In time, I hope to approach his standards of excellence. On a more personal level, many others have been of assistance. Without the loyal and unswerving support of Ms. Ellen Sanders, my first three years of study at KSU would have been impossible. I would like to thank my father, Major F. W. Greenhut, U.S. Army (Ret.), for awakening my interest in things military, and my mother, Julia Mehlman Greenhut, M. D. who, even though she didn't want me to be "that kind of doctor" nonetheless provided generous and essential financial support. My children, Wendy and David, to whom this dissertation is dedicated, unknowingly provided an anchor which kept me steady in my work. Finally, great praise to my wife, Susan, whose contribution to me and to my work is truly unmeasurable.